Let B=number of beads. B-(B/4+B/3)=30; B-(3/12+4/12)B=B-7B/12=5B/12=30; B=12*30/5=72.
One third of 72=72/3=24 beads are worth 120, so 72 are worth 3*120=360.
This answer assumes the question means 1/3 of the original number of beads and not a third of what remains.
If the question means a third of the remaining beads are used on the second day, we have a different problem:
B-B/4 on the first day leaves 3B/4 and a third of this is B/4. So the number of beads used on both days is B/4+B/4=B/2. So B-B/2=B/2=30 and B=60. A third of 60 beads is 20, so 20 beads cost 120 and 60 beads cost 3*120=360, same answer as before.
The answers are the same because of the way the cost is worked out. If a third of the beads cost 120, then 3 thirds will cost 360, no matter what. The cost of one bead will be different: in the first case 72 beads cost 360 so 1 bead costs 360/72=5. In the second case 60 beads cost 360 so 1 bead costs 360/60=6.